Métodos para resolução eficiente de problemas de layout - Cellin, Bernardo de Polli (2017)
In production systems where a decrease in production costs is seen as a key part of the competitive strategy, Optimization is an important tool to assist companies in this process of survival and expansion in the market. There are many Layout problems in Industry, which are optimization problems that are characterized by the physical arrangement of facilities along a given area, forming a layout. Layout problems are difficult and complex to solve, from a computational point of view. For economic and academic reasons, Layout Problems have been studied for decades. This dissertation proposes heuristic and hybrid methods for solving some of these problems found in the literature, such as Facility Layout Problems on two or more parallel lines. More specifically, methods based on the metaheuristics Simulated Annealing, Variable Neighborhood Search and Iterated Local are implemented to solve such problems. In addition to meta-heuristics, a Linear Programming model is also used.